Forensic characteristics of chest injuries among subjects who died in road traffic accidents - Slović, Živana S.; Vitošević, Katarina; Todorović, Danijela; Todorović, Miloš (Vojnosanitetski pregled, 2021)
Background/Aim. In road traffic accidents, chest injuries are a critical factor since death usually occurs as a result of injuries to the heart and lungs, flail chest, pneumothorax, exsanguination, etc. The aim of this study was to analyze the most vulnerable subjects in road accidents, as well as the most frequent and most significant types of chest injuries sustained by different categories of subjects, and to examine the relevance of certain injuries or factors to outliving the injuries. Methods. The autopsy, the retrospective, and the cross-sectional study were performed at the Clinical Centre of Kragujevac, Department of Forensic Medicine and Toxicology. The study included all participants in road traffic accidents on the territory of Kragujevac and the surrounding area who died from the injuries sustained from the accidents or due to complications of the injuries during the period from 2001 to 2016. The subjects were divided into the following groups: pedestrians, motor vehicle drivers, front-seat passengers, back-seat passengers, bicyclists, motorcyclists, and tractor drivers. The occurrence of injuries in three regions of the body (chest, head, and abdomen) was analyzed in all the subjects. Results. The study included 525 subjects who died due to the injuries sustained in traffic accidents, which makes up to 38.4% of the total number of 1,366 autopsy cases covered by the study period. The average age of the subjects was 52 ± 19 years. The study sample consisted of 391 (74.5%) men and 134 (25.5%) women. The most vulnerable subjects were pedestrians (220, i.e. 41.9%), followed by motor vehicle drivers (98, i.e. 18.7%), front-seat passengers (79, i.e. 15%), motorcyclists (39, i.e. 7.4%), bicyclists (38, i.e. 7.2%), back-seat passengers (29, i.e. 5.5%) and tractor drivers (22, i.e. 4.2%). Chest injuries were identified in 408 subjects (77.7%), while the most frequent type of injury was rib fracture, observed in two-thirds of the sample. Out of the total number, 291 (55.4%) subjects died at the scene of the accident or on their way to the hospital, while 234 (44.6%) of them outlived injuries for a certain period of time. Drivers exhibited the highest risk of dying at the scene, while bicyclists outlived their injuries more frequently. Conclusion. Chest injuries are very common in subjects who died at the scene of the road traffic accident.